Influence of Scarcity Marketing and Perceived Value on Buying Decision Moderated by Collaboration - Didit, Didit Setiawan; Diansyah, Diansyah; Kamaruddin, Muhammad Junaid (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to examine the influence of scarcity marketing and customer perceived value on purchasing decisions, with brand collaboration—specifically with the Aerostreet shoe brand—acting as a moderating variable. As consumer behavior continues to evolve in the digital era, understanding the psychological triggers that drive purchasing decisions becomes essential for marketers. This study focuses on how limited availability (scarcity) and perceived benefits (value) can influence buyer intent and how a well-known local brand collaboration may amplify these effects. Methodology/approach: The study uses a quantitative research approach, with data collected through an online questionnaire targeting Aerostreet shoe consumers in Jakarta. A total of 121 respondents were selected using the Slovin formula for large, indefinite populations. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS application to assess the relationships among the variables. Results/findings: The analysis reveals that both scarcity marketing and customer perceived value have a positive and significant influence on purchasing decisions. Furthermore, the presence of a brand collaboration with Aerostreet serves as a moderating variable that strengthens the impact of these marketing strategies on consumer behavior. Conclusion: Scarcity and perceived value are key drivers in consumer decision-making, and their influence can be enhanced through strategic brand collaborations such as those involving Aerostreet. Limitations: The study is limited to a specific brand and demographic region, so generalizability may be constrained. Contribution: This study provides practical insights for marketers on leveraging scarcity and value perceptions, especially when paired with brand collaborations, to increase consumer engagement and purchase intent.